A randomized, single dose, two treatment, two period, crossover bioequivalence study of cefixime (as trihydrate) suspension in healthy participants comparing Acacime® suspension produced by ACAI / Iraq to Suprax® suspension produced by Hikma / Jordan - Ahmad Ismail Al-Shathar; Samir Hasson Aziz (College of Pharmacy / Mustansiriyah University, 2018)
Formulation of drugs affects their access into human body, thus bioequivalence studies are conducted to assess therapeutic equivalence between medicines which are produced by different manufacturers. In this study, bioequivalence of two cefixime formulations as powder for suspension, Acacime® manufactured by Arab Co. for Antibiotics Industries (ACAI) / Iraq, and Suprax®, manufactured by the Jordanian Co., Hikma, is tested. Twenty-four subjects had participated in the study which was designed as, a randomized, single dose, two period, crossover study. Cefixime concentrations in plasma were measured by validated bioanalytical method, using high-performance liquid chromatography with UV detection. The determined pharmacokinetics parameters were Cmax, AUC0-t and AUC0-∞ for cefixime. The mean results obtained for Acacime® and Suprax® were, for C max: 2.736 and 2.395 µg/ml, for AUC0-t: 16.787 and 16.579 µg/ml*h and, for AUC0-∞: 21.011 and 21.685 µg/ml*h, respectively. The 90% confidence intervals for AUC0-t, AUC0-∞ and Cmax were 92.3 - 110.8%, 84.8 - 102.7% and 96.3 - 117.9% respectively. This study revealed that both products were comparable in efficacy and safety, so they are considered as bioequivalent products and can be used interchangeably. الخلاصة